Mutations in CLDN2 Are Not a Common Cause of Pediatric Idiopathic Hypercalciuria in Canada. (May 2022) - Ulrich, Emma H.; Harvey, Elizabeth; Morgan, Catherine J.; Pinsk, Maury; Erickson, Robin; Robinson, Lisa A.; Alexander, R. Todd
Background: Hypercalciuria is the most common risk factor for kidney stone formation, including in pediatric patients. However, the etiology is often unknown and children are frequently diagnosed with idiopathic hypercalciuria. Nearly 50% of children with hypercalciuria have a first-degree relative with kidney stones, suggesting a strong genetic basis for this disease. A failure of calcium reabsorption from the proximal nephron is implicated in the pathogenesis of hypercalciuria. Claudin-2 is a tight junction protein abundantly expressed in the proximal tubule. It confers paracellular permeability to calcium that is essential for transport across the proximal tubule where the majority of filtered calcium is reabsorbed. Objective: Our objective was to examine the frequency of coding variations in CLDN2 in a cohort of children with idiopathic hypercalciuria. Design: Mixed method including retrospective chart review and patient interview, followed by genetic sequencing. Setting: Three tertiary care centers in Canada. Patients: Children (age 1-18 years) with idiopathic hypercalciuria. Patients with other causes of hypercalciuria were excluded. Methods: Data were collected from 40 patients with idiopathic hypercalciuria. Informed consent to collect DNA was obtained from 13 patients, and the final and only coding exon of CLDN2 was sequenced. Results: The majority of patients were male, white, and had a positive family history of kidney stones. Parathyroid hormone levels were significantly lower than the reference range ( P < .001). The levels of 1, 25-dihydroxyvitamin D were also significantly higher in our patient cohort, relative to the reference range ( P < .001). Sequence analysis of CLDN2 did not identify any coding variations. Limitations: Sequencing analysis was limited to the final coding exon and small sample size. Conclusions: CLDN2 coding variations are not a common cause of idiopathic hypercalciuria in Canadian children. Further study is needed to determine the causes of hypercalciuria in pediatric patients and develop targeted therapies.